LEGAL PROTECTION OF COPYRIGHT FOR LITERARY WORKS OF BOOKS FROM ACTS OF ONLINE PIRACY IN PDF VERSIONS VIA THE WHATSAPP APPLICATION - Putra, Regina Roidatun Sari; Rahmayani, Nuzul; Nazar, Jasman (DE'RECHTSSTAAT, 2024)
Cases of piracy are currently getting higher and more common, ranging from piracy of music, films, software, data bases, works of literature, books, science, and pictures or photography. The ranking of piracy in Indonesia, especially copyright, is the third largest in the world. Piracy seems to have become a culture and difficult to overcome, especially in Indonesia. If you look at the definition of book piracy that is usually listed in every book, namely efforts to reproduce books by printing, photocopying or other means without obtaining written permission from the publisher of the book concerned, then you will find many parties who consciously or unknowingly can be called pirates. In Article 40 Paragraph (1) Letter (a) of the Law of the Republic of Indonesia Number 28 of 2014 concerning Copyright, a book is one of the creations that is protected by Copyright.The formulation of the problem in this study is How can a Pdf version of a literary work be said to be copyright piracy? And how is the legal protection for creators against piracy of Pdf versions of literary works through the WhatsApp application?. The research method that the writer uses is the normative juridical method, where the writer must collect data from written regulations so that this research is very closely related to the library because it will require secondary data from the library.Based on the results of the research that the authors conducted on this problem, that law enforcement against Copyright infringement is very important, considering that the development of Copyright protection and legal protection of Copyright for creators is still lacking, where there are still many obstacles that arise in law enforcement, even though it has been legal efforts are made by the parties, as well as the application of legal sanctions against copyright infringement.